2016
DOI: 10.3390/ijerph13101021
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RACK1 Promotes Metastasis by Enhancing Epithelial-Mesenchymal Transition and Predicts Poor Prognosis in Human Glioma

Abstract: Emerging studies show that dysregulation of the receptor of activated protein kinase C1 (RACK1) plays a crucial role in tumorigenesis and progression of various cancers. However, the biological function and underlying mechanism of RACK1 in glioma remains poorly defined. Here, we found that RACK1 was significantly up-regulated in glioma tissues compared with normal brain tissues, being closely related to clinical stage of glioma both in mRNA and protein levels. Moreover, Kaplan-Meier analysis demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Moreover, several studies have shown that pY23-Anxa2 promotes cancer cell invasion and metastasis through enhancing epithelial-mesenchymal transition (EMT) [46,60,70]. Likewise, Rack1 has also been reported to regulate EMT and contribute cancer metastasis [71,72]. Drug-resistant cells are always associated with EMT phenotype [73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have shown that pY23-Anxa2 promotes cancer cell invasion and metastasis through enhancing epithelial-mesenchymal transition (EMT) [46,60,70]. Likewise, Rack1 has also been reported to regulate EMT and contribute cancer metastasis [71,72]. Drug-resistant cells are always associated with EMT phenotype [73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…In fact both in vitro and in vivo studies have shown that RACK 1 promotes the proliferation, invasion and metastasis of breast cancer (57) and remains one of the independent predictors for poor clinical outcome in breast cancer (58). Perhaps RACK1 was not only associated with breast cancer malignancy, but its overexpression is implicated in the growth and metastasis of several other cancer types such as lung cancer, gliomas, colon cancer, prostate cancer, liver cancer, epithelial ovarian cancer and squamous cell carcinoma of the esophagus (59). Finally, the top ve proteins found to be upregulated in our analysis included Filamin A.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, GNB2L1 has been reported to regulate EMT in different kinds of cancers including esophageal squamous cell carcinoma and Glioma [ 22 , 23 ]. Intriguingly, although previous studies revealed that GNB2L1 led to the protein level change of different EMT-related proteins in WB and IHC analysis, they didn’t observe similar changes in mRNA levels of these proteins [ 22 , 23 ]. Consistent with their results, we also failed to detect the changes of mRNA levels resulted from GNB2L1 in the chemoresistance of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%